LATE GLACIAL AND HOLOCENE EROSIONAL DISSECTION AND FILL IN THE TEMPORAL (EPHEMERAL) STREAM VALLEY ON THE RIGHT BANK OF THE SELENGA RIVER - Yu. V. Ryzhov; V. A. Golubtsov; M. V. Smirnov (Геодинамика и тектонофизика, 2024)
The structure, composition and cut and fill sequence of the Late Glacial and Holocene erosional landforms in the Kuitunka River basin on the right bank of the Selenga River were studied based on a detailed analysis and radiocarbon dating of the soil-sedimentary sequence in the Studenyi Klyuch 2 and Kovalev Pad’ sections. A correlation was carried out between seven sections in the intermittent stream valleys in the Kuitunka River basin. There are three episodes of the Late Glacial and Holocene cutting dated back to ~18–17, ~14.7–14.3, and 0.25–0 cal. kyr BP (ka BP). There are distinguished the periods of colluvial, colluvial-deluvial and aeolian-deluvial sediment deposition in the intermittent stream valleys (17.0–14.7 ka BP) and predominantly aeolian-deluvial loess-like sediment accumulation involving pedogenetic stages (14.30–0.25 ka BP). The climatic warming and humidification led to a decrease in sedimentation rate, prevalence of loessification processes in formation of loess-like deposits, and formation of organic–accumulative soil horizons of different thicknesses. The Late Glacial warming, comparable to the Bølling – Allerød Interstadial (14.3–12.9 ka BP) and the Holocene (11.7–0 ka BP), is characterized by a dynamic change in the stages of loess-like deposit accumulation and pedogenesis. The Younger Dryas cooling (12.9–11.7 ka BP) is associated with the activation of aeolian and cryogenic processes and a short phase of pedogenesis. It was revealed that the most frequent changes in sedimentary phases and soil formation occurred during the Late Glacial Interstadial and the Early (11.7–8.2 ka BP) Holocene. The Middle Holocene (8.2–4.2 ka BP) is characterized by a decrease in the rate of accumulation of intermittent-stream valley loess-like bottom deposits and a long-term (several ka) active pedogenetic process. The cross-sections of the Late Holocene (last 4.2 ka BP) draws and valley-bottom gullies exhibit the stages of pedogenesis (4.2–1.0 ka BP), activation of erosion–accumulation processes (1.00–0.25 ka), gullying, accelerated erosion, and accumulation (last 0.25 ka BP).